Enhancing the B2B Selling Process Through Social Media - Bercier, Olivier (Université d'Ottawa / University of Ottawa, 2020)
This study provides insights into understanding social media utilization in the B2B selling process. More specifically, this research details how the different functional blocks of social media are leveraged to benefit the various stages of the selling process. This study adopts a multiple case study design, including six cases from technology-related Canadian firms. Overall, findings show that the functional blocks of social media are mostly leveraged in the prospecting and preapproach stages of the selling process. Furthermore, the marketing strategy of the seller firm seems to influence which functional blocks are leveraged in the process. At last, findings also show that social media should be complemented by analytical tools and traditional media to optimize the selling process with higher lead quality and to facilitate trust-building with potential and existing customers
Keywords: social media; B2B; sales; selling process; business-to-business